2018
DOI: 10.3800/pbr.13.75
|View full text |Cite
|
Sign up to set email alerts
|

Possible aplanochytrid (Labyrinthulea) prey detected using 18S metagenetic diet analysis in the key copepod species <i>Calanus sinicus</i> in the coastal waters of the subtropical western North Pacific

Abstract: Metagenetic diet analyses of the 18S V9 region were conducted in 40 adult female Calanus sinicus during winter in Tosa Bay (Japan). The majority of prey items were small crustaceans (of Copepoda and Cirripedia) and diatoms, taxa that are dominant in the environment and have been previously reported as important prey items of Calanus. The abundance of sequences attributable to Dinophyta and Chlorophyta was significantly lower in C. sinicus gut contents than in environmental plankton communities, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Aplanochytrids have been detected in the gut and fecal pellets of copepods and salps in the tropical Indian and North Pacific Oceans [34, 37, 39, 65]. Hirai et al (2018) [39] reported that aplanochytrids, which were recognized by 18S rDNA metagenomic analysis, were possibly the major food source of Calanus sinicus , a large copepod common in the coastal waters of the subtropical western North Pacific [66]. The proportion of Aplanochytrium was higher in gut contents than in environmental samples, suggesting that C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aplanochytrids have been detected in the gut and fecal pellets of copepods and salps in the tropical Indian and North Pacific Oceans [34, 37, 39, 65]. Hirai et al (2018) [39] reported that aplanochytrids, which were recognized by 18S rDNA metagenomic analysis, were possibly the major food source of Calanus sinicus , a large copepod common in the coastal waters of the subtropical western North Pacific [66]. The proportion of Aplanochytrium was higher in gut contents than in environmental samples, suggesting that C .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of Aplanochytrium was higher in gut contents than in environmental samples, suggesting that C . sinicus positively selected aplanochytrids as prey [39]. This copepod was shown to actively capture particles with a diameter of 20–50 μm, but few particles smaller than 10 μm [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calanus sinicus is one of the important secondary producers that connect primary producers with higher trophic levels in the coastal area of the Japan Sea, although C. sinicus is known to prey on heterotrophic plankton in addition to phytoplankton (Hirai et al, 2018;Yi et al, 2017;Uye and Yamamoto, 1995). The δ 15 N values of C. sinicus (6.9 ± 1.2‰) are consistent with this scenario: their δ 15 N values are intermediate between those of particulate organic matter (POM) in coastal areas of the Japan Sea (around 2-6‰) (Kogure, 2004;Antonio et al, 2012) and predatory fishes such as Japanese anchovy (8.9-11.7‰) (Tanaka et al, 2008) and Japanese sardines (9.4 ± 0.7‰) (Ohshimo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For copepod gut bacterial community analyses, a method of dissecting the gut from individual specimens has been commonly used [ 19 ]. This method has been used for large species such as Calanus (2–3 mm of prosomal length); however, it is difficult to apply it to small-sized species [ 20 , 21 ]. Although the DNA analysis methods of the gut contents of small zooplankton (rotifers, under 400 μm) have been proposed [ 22 ], zooplankton species-specific differences, such as exoskeleton hardness, must be considered, and methods that can be applied to small-sized copepod species (700 μm–1 mm of prosomal length) are still required [ 23 ].…”
Section: Introductionmentioning
confidence: 99%